A Computational Comparison of Flow and Pressure Fields in Axial and Reverse Flow Cyclone Separators - SAKİN , Ali (International Journal of Computational and Experimental Science and Engineering, 2017)
Cyclones are separation devices that use centrifugal forces to remove dense phases from two phase flows. There are many application areas of cyclone separators ranging from industrial processes to domestic applications due to their simple structure and lack of movable components. For this reason, they are commonly preferred where two phase fluid flow accommodated and separation is required. In this study, axial and reverse flow tangential inlet novel cyclone geometries were introduced to configure different separation space and to reduce pressure drop in comparison with traditional cyclone geometry. Although the construction of a cyclone is simple, the cyclone flow and separation process are very complex. Therefore, CFD is quite appropriate provided that the proper mathematical models and computational techniques are used. 3-D and unsteady governing equations were used for the turbulent cyclone flow. Hexahedral meshed domain was solved by using Fluent CFD software. Eulerian approach was used to solve the flow field and transient Reynolds Stress Model (RSM) with the scalable wall function. Lagrangian approach with DPM (Discrete Phase Model) was used to calculate discrete phase by releasing particles from inlet surface. CFD calculations were run for different geometric configurations in order to analyze performance of cyclones in terms of pressure drop, cut-off diameter and grade efficiency. Axial and tangential velocity profiles are presented at defined sections. The computational results of pressure drop, velocity field and separation efficiency were also compared for the axial and reverse flow cyclones at the same flow rates.